The Role of Farmer Groups in Increasing the Income of Tomato Farmers in Padende Village, Central Sulawesi, Indonesia - Rifan, Moh; Jaya, Andi Herman; Tallesang, Mukhtar; Musdayati, M.; Jokolelono, Eko (Golden Ratio of Data in Summary, 2025)
This study aims to examine the role of farmer groups in increasing the income of tomato farmers before and after joining such groups. The research was conducted using a descriptive research method in Padende Village, Marawola District. The findings indicate that the involvement of MBKM students as village facilitators has positively impacted tomato farmers by providing targeted training. This training enabled the farmers to maximize production and sell their tomatoes directly in the primary market. The role of farmer groups in improving income is considered significant, as the tomato farmers in Padende Village are part of a combined farmer group. This group receives support from the village government, particularly in seed assistance. As a result, tomato farmers' income increased notably, reaching IDR 3,500,000 in 2023 from managing 1 hectare of land.